Effect of foliage-tannins on feeding activity in goats - Silanikove N.; Gilboa N.; Nitsan Z.; Perevolotsky A. (Recent advances in small ruminant nutrition, 1997)
The concept that tannins in foliage reduce the voluntary intake of foliage by goats by evoking negative postingestive responses was examined. Meals and breaks between meals of goats fed high-tannin foliage were cyclic; the first meal within each cycle was the longest. Once-daily supplementation of polyethylene glycol (PEG) with a molecular weight of 4000, a tannin-binding agent, increased the duration of feeding activity and decreased the duration of breaks between meals. Tha cyclic feeding behaviour could be associated with development of food aversion due to interaction of tannins with the rumen epithelium.
Seminar of the FAO-CIHEAM Network of Cooperative Research on Sheep and Goats, Subnetwork on Nutrition, 24-26 Oct 1996, Rabat (Morocco)